First detection of West Caucasian Bat Lyssavirus infection in a domestic cat, Italy, 2020: ecological and sanitary implications. (March 2022) - Leopardi, S.; Barneschi, E.; Manna, G.; Zecchin, B.; Priori, P.; Drzewnioková, P.; Festa, F.; Lombardo, A.; Parca, F.; Scaravelli, D.; Ponti, A. Maroni; De Benedictis, P.
Abstract : Purpose: While Europe is mostly free from terrestrial rabies, five bat lyssaviruses may cause the same clinical disease in mammals. In June 2020, we diagnosed the infection with West Caucasian Bat Lyssavirus (WCBV) in a domestic cat from Arezzo city (Italy). Methods & Materials: We diagnosed the case according to OIE standards, using fluorescence antibody test, rRT-PCR and sequencing of partial N gene. We performed whole genome sequencing through a metagenomics approach. In Arezzo, we applied control measures indicated by national regulations and carried out an epidemiological investigation to trace the contacts between the infected cat, people and other animals in the 10 days preceding the onset of disease. We performed visual inspections, bioacoustics analyses and camera trapping to investigate a possible interface between cats and bats and performed active and passive surveillance in these animals to trace the source of infection. Results: Italian WCBV retained high identity across the whole-genome with the only other isolate found in 2002 from a Russian bent-winged bat ( Miniopterus schreibersii ) (GB EF614258). We identified 11 contacts, six persons that received full PEP, plus a dog and four cats that underwent six months of quarantine. They all remain healthy one year passed exposure. We identified a group of bent-winged bats in a tunnel nearby the cat's house showing antibodies neutralizing WCBV across four sampling occasions, but no virus in salivary swabs. Bat carcasses from different species collected across the country were all negative. Conclusion: We described the first case of WCBV in a non-flying mammal, an Italian cat showing neurological signs and aggressive behaviour. This event highlights the lack of international guidelines against divergent lyssaviruses in the absence of preventive and therapeutic measures. Fortunately, we noticed no secondary cases and contacts remained healthy. The Italian WCBV retains high identity with the reference strain, showing no signs of geographical clustering or adaptation to a new host. Results from our investigation indicate bent-winged bats as the most probable source of infection, testifying the bat-human encroachment in urban areas and confirming that free-ranging cats are a potential hazard for public health other than for the conservation of bats.